Traditional foods in rural villages of the Central Dalmatian islands of Brač, Vis and Hvar - Duvnjak, Neven; Macan, Deni (Socio.hu Társadalomtudományi Szemle, 2015)
In this paper we research the presence of traditional forms of approach to food in rural villages of Dalmatian islands in the times when some of these forms are forgotten, but others have become gastronomic specialities crucial in offers to tourists. The topic of the research is perceptions which inhabitants of villages have of traditional diet as a cultural phenomenon, and how they experience the influence of processes of modernization and postmodernization on nourishment tradition. The theoretical framework assumes a developmental approach, which implies that the current eating needs are the products of a long lasting historical development that includes the presence of changes and periods of stability. Main eating practices (traditional, modern, and postmodern) we defined using content analysis of Dalmatian cook books. Analysis shows that traditional recipes are dedicated to domestic food, which has been prepared for a number of years in the same manner. Therefore, purchasing fresh food and every day cooking is recommended, including spending much time in preparing food. A key characteristic of modern nourishment is using industrially processed food, and postmodern nourishment is denoted by the openness to new foodstuffs and dishes with a tendency for experimenting. On the basis of notions defined in this way, we will determine the main characteristics of nourishment of rural villages: the look of daily meals, basic daily groceries, and dominant ways of food preparing. The ethnographic part of the paper includes field notes that were recorded during informal conversations with 26 residents of the islands Brač, Hvar and Vis. According to the ethnographic research the cuisine of the rural villages is strongly linked to tradition. The modern approach appears sporadically, and the postmodern approach does not appear at all. The traditional rural diet is characterized by simplicity and is mostly based on products from family production. Methods of food preparation and consumption continue to be sustained through the inherited traditional habits. Good opportunities for the future development of traditional island cuisine lie in maintaining the uniqueness and by means of integral sustainability assisting a postmodern ecological world view, which emphasizes the restoration of local knowledge. Keywords: Dalmatian islands, rural villages, traditional, modern and postmodern forms of food and diet